A non-redundant data set of nanobody-antigen crystal structures - Zavrtanik, Uroš (Data Brief, 2019)
A non-redundant data set of nanobody-antigen crystal structures is presented. The data set consists of a collection of cleaned pdb files which can be readily used as an input with most automatic analysis software. The accompanying data also include nanobody amino acid sequences with the annotated CDR regions. In the tabular format, we provide data on the interaction properties for each complex such as number of intermolecular interactions, experimental affinity and changes of the solvent accessible area. We also include the data regarding the surface composition of all nanobody and antigen molecules (surface occurrence of each amino acid type and its secondary structure). The data may be used for further structural bioinformatic studies of nanobodies and as the reference data when performing comparisons with the conventional antibodies.